Radiation Protection, Safety and Security Issues in Ghana. Issue 3 (November 2016) - Boadu, Mary; Emi-Reynolds, Geoffrey; Amoako, Joseph Kwabena; Akrobortu, Emmanuel; Hasford, Francis
Abstract : Abstract: Although the use of radioisotopes in Ghana began in 1952, the Radiation Protection Board of Ghana was established in 1993 and served as the national competent authority for authorization and inspection of practices and activities involving radiation sources until 2015. The law has been superseded by an Act of Parliament, Act 895 of 2015, mandating the Nuclear Regulatory Authority of Ghana to take charge of the regulation of radiation sources and their applications. The Radiation Protection Institute in Ghana provided technical support to the regulatory authority. Regulatory and service activities that were undertaken by the Institute include issuance of permits for handling of a radiation sources, authorization and inspection of radiation sources, radiation safety assessment, safety assessment of cellular signal towers, and calibration of radiation-emitting equipment. Practices and activities involving application of radiation are brought under regulatory control in the country through supervision by the national competent authority.